Coping Strategies in Analyzing the Stress Impact of Online Gambling Addiction for Children and Adults - Rizki, Akbar; Ishar, Meilia; Khairani, Khairani (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Increased internet accessibility has opened up opportunities for people to engage in various types of gaming, such as poker, online casinos, sports betting, and slot machines. This research aims to describe coping strategies for minimizing the stressful impact of online gambling addiction. This research uses a qualitative approach with a literature study. The results of this research reveal that online gambling addiction has a serious impact on people's stress levels in Indonesia. Factors such as financial losses, uncertainty of gambling outcomes, and interpersonal tension due to excessive involvement in online gambling activities are the main causes of increased stress levels. Coping strategies to minimize the stressful impact of online gambling addiction are achieved by focusing efforts on financial management, social support, and developing entertainment alternatives. The study found that dependence on online gambling triggers significant stress in both children and adults. The stress was caused by a variety of factors, including financial loss, impaired social relationships, and psychological impacts such as anxiety and depression.